2020
DOI: 10.36076/ppj.2020/23/423
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Versus Bupivacaine in the Treatment of Headache with Intranasal Sphenopalatine Nerve Block

Abstract: Background: Intranasal sphenopalatine ganglion (SPG) block has been shown to be an effective treatment for headaches. Multiple therapeutic agents have been studied, although the wide availability and low cost of lidocaine and bupivacaine have made them attractive treatment options. To the authors knowledge, no study has yet demonstrated superiority of one anesthetic over the other. Objective: To determine the efficacy of lidocaine versus bupivacaine when performing intranasal sphenopalatine ganglion (SPG) bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…There are few headto-head studies comparing the efficacy of different medications, and the existing findings fail to demonstrate a superior agent. A retrospective study evaluating 386 SPG blocks for headache found no difference between bupivacaine and lidocaine for pain reduction [21]. A randomized controlled study of 90 patients compared SPG block with lidocaine 2%, lidocaine 5%, and bupivacaine 0.5% for treating post-dural puncture headache and again found no difference between the groups [22].…”
Section: Discussionmentioning
confidence: 99%
“…There are few headto-head studies comparing the efficacy of different medications, and the existing findings fail to demonstrate a superior agent. A retrospective study evaluating 386 SPG blocks for headache found no difference between bupivacaine and lidocaine for pain reduction [21]. A randomized controlled study of 90 patients compared SPG block with lidocaine 2%, lidocaine 5%, and bupivacaine 0.5% for treating post-dural puncture headache and again found no difference between the groups [22].…”
Section: Discussionmentioning
confidence: 99%
“…д.) [21,22] или же другой местный анестетик [23]. Оставшиеся 5 исследований [8][9][10][11][12], которые соответствовали критериям включения и исключения, составили основу данного метаанализа.…”
Section: результаты отбор исследованийunclassified
“…Юрьева, Д.В. Заболотский Эффективность применения крылонебной блокады с целью обезболивания у взрослых: систематический обзор и метаанализ В нашем исследовании отсутствие плацебо в группах сравнения или сочетание КНБ с другим периферическим блоком в некоторых исследованиях сделало невозможным включение их в метаанализ и статистическую обработку [15,[21][22][23]38]. Тем не менее хотелось бы остановиться на результатах данных публикаций подробнее.…”
unclassified
See 1 more Smart Citation